Chromatic polynomials of signed graphs - Utomo, Charissa Irene (Nanyang Technological University, 2023)
Signed graphs are currently enjoying intense interest from the combinatorial community due to various mathematical breakthroughs that relied on results about signed graphs. We expose the discrepancies in the computation of the chromatic polynomials of signed Complete Graphs and Petersen Graphs, presented in the research paper titled “The Chromatic Polynomials of Signed Petersen Graphs” by Beck et al.